Structural insights into the binding mechanism of Plasmodium falciparum exported Hsp40-Hsp70 chaperone pair. (December 2019) - Behl, Ankita; Mishra, Prakash Chandra
Graphical abstract: Highlights: Multiple template based approach gave a reliable model of Plasmodium falciparum Hsp40 'PFA0660w'. PFA0660w shows bipartite interaction with PfHsp70-x. G/F region of PFA060w interacts transiently with substrate binding domain of PfHsp70-x. The peptide binding cleft of PFA0660w is larger than its counterparts in higher eukaryotes. PFA0660w may have different mechanism for binding with substrate and PfHsp70-x. Abstract: Expression of heat shock proteins in Plasmodium falciparum (Pf) increases during febrile episodes to play key roles in several necessary cellular processes. 'PFA0660w-PfHsp70-x', an exported chaperone pair is known to co-localize to specialized intracellular structures termed J-dots, and has been implicated in trafficking of the major virulence factor, PfEMP1 ( Plasmodium falciparum erythrocyte membrane protein 1) across the host cell. This article highlights for the first time detailed structural analysis of PFA0660w-PfHsp70-x chaperone pair to better understand their binding mechanism. Here, we have modeled reliable molecular structures for the complete conserved region of PFA0660w and PfHsp70-x. These structures were evaluated by different structure verification tools followed by molecular dynamics (MD) simulations. The model of PFA0660w was subjected to docking with PfHsp70-x using Haddock to reveal a number of residues crucial for their bipartite interaction, and also performed MD simulations on the complex. The peptide binding clefts of PFA0660w and its other Plasmodium species homologs were found to be bigger than their counterparts in higher eukaryotes like yeast, humans and C. parvum . Based on our results, we propose a model for PFA0660w-PfHsp70-x interaction and a mechanism of substrate binding, and compare it with its dimeric human counterparts. Owing to these striking structural differences between the host and parasite chaperones, such information on the essential Hsp40 and its partner Hsp70 may form the basis for rational drug design against fatal malaria.